Spontaneous and Adenosine‐Induced Pulmonary Vein Reconnection After Cryoballoon Ablation with the Second‐Generation Device. (2nd May 2014) - CICONTE, GIUSEPPE; CHIERCHIA, GIAN‐BATTISTA; DE ASMUNDIS, CARLO; SIEIRA, JUAN; CONTE, GIULIO; JULIÁ, JUSTO; DI GIOVANNI, GIACOMO; WAUTERS, KRISTEL; BALTOGIANNIS, GIANNIS; SAITOH, YUKIO; MUGNAI, GIACOMO; CATANZARITI, DOMENICO; et al.
Second‐generation Cryoballoon Ablation and Pulmonary Vein Reconnections Introduction Longer observational time and adenosine challenge have proven to be able to detect pulmonary vein (PV) reconnections. The aim of this study was to assess incidence of spontaneous and adenosine‐induced PV reconnection after ablation with second‐generation cryoballoon (CB‐Adv). Methods and Results Fifty consecutive patients (76% male, mean age 60.5 ± 11.9 years) having undergone PV isolation (PVI) using the CB‐Adv were enrolled. After isolation, reconnections were evaluated using the Achieve catheter over 30 minutes observation and adenosine administration during isoproterenol infusion (adenosine challenge). Among 200 PVs, isolation was achieved in 190 (95%) during the first application. Lower nadir temperature and longer rewarming time were associated with successful PVI (P = 0.02 and 0.04). Spontaneous (4 veins) and adenosine‐induced (4 veins) PV reconnections occurred in the 4% of initially isolated veins (8 veins) in 6 patients (12%). At receiver–operator curve analysis, nadir temperature <–51 °C and rewarming time >28 seconds identified absence of reconnections (sensitivity 100% and 87%, area under the curve 0.75 and 0.72). Patients with right‐sided early branching frequently experienced reconnections (P < 0.01). After a mean follow‐up of 7.0 ± 1.7 months, 86% of patients were free from atrial fibrillation. None of those with PV reconnections experienced recurrences. Conclusions The incidence of spontaneous and adenosine‐induced PV reconnection following ablation with the novel CB‐Adv is very low occurring in 4% of initially isolated veins. Nadir temperature <−51 °C and rewarming time >28 seconds identified absence of acute reconnections, thus avoiding prolonged waiting time and adenosine challenge in such cases.